Relationships between external loads, sRPE-load, and self-reported soreness across a men’s collegiate soccer season - Kuhlman, Nicholas; Jones, Margaret; Jagim, Andrew; Feit, Mary; Aziz, Richard; Crabill, Thomas; Fields, Jennifer (Biology of Sport, 2023)
The purpose was to examine relationships between external loads (ELs), perceived exertion, and soreness. Collegiate men soccer players (n = 19) were monitored for 72 sessions (training: n = 53; matches: n = 19). Likert scale assessments (0–6) of lower body soreness were collected prior to each session, and ELs were collected using positional monitoring technology. Session rate of perceived exertion (sRPE-load) was calculated by multiplying perceived exertion values (Borg CR-10 Scale) by respective session duration to determine internal load. Multiple analyses of variance were used to determine differences in ELs across seasons (preseason, in-season, post-season) and sessions (training, match). Bivariate Pearson correlation coefficients and linear regression analyses were used to evaluate relationships among soreness, ELs, and sRPE-load. Greatest ELs were observed during pre-season and post-season phases (p < 0.001). Sessions with high perceived exertion and low soreness were associated with higher ELs (p < 0.05). Duration (t = 16.13), total distance (t = 9.17), sprint distance (t = 7.54), player load (t = 4.22), top speed (t = 4.69), and acceleration (t = 2.02) positively predicted sRPE-load (F = 412.9, p < 0.001, R2 = 0.75). Soreness was weakly and trivially correlated with ELs (p < 0.05). The very strong relationship between ELs and sRPE-load highlights the utility of sRPE-load as a practical means to estimate workload; however, more research into the relationship between soreness and workload is warranted.